Regulatory considerations for the clinical and research use of transcranial direct current stimulation (tDCS): Review and recommendations from an expert panel - Fregni, F.; Nitsche, M. A.; Loo, C. K.; Brunoni, A. R.; Marangolo, P.; Leite, J.; Carvalho, S.; Bolognini, N.; Caumo, W.; Paik, N. J.; Simis, M.; Ueda, K.; et al. (Clinical research and regulatory affairs, 2015)
Abstract The field of transcranial electrical stimulation (tES) has experienced significant growth in the past 15 years. One of the tES techniques leading this increased interest is transcranial direct current stimulation (tDCS). Significant research efforts have been devoted to determining the clinical potential of tDCS in humans. Despite the promising results obtained with tDCS in basic and clinical neuroscience, further progress has been impeded by a lack of clarity on international regulatory pathways. Therefore, a group of research and clinician experts on tDCS were convened to review the research and clinical use of tDCS. This report reviews the regulatory status of tDCS and summarizes the results according to research, off-label, and compassionate use of tDCS in the following countries: Australia, Brazil, France, Germany, India, Iran, Italy, Portugal, South Korea, Taiwan, and the US. Research use, off label treatment, and compassionate use of tDCS are employed in most of the countries reviewed in this study. It is critical that a global or local effort is organized to pursue definite evidence to either approve and regulate or restrict the use of tDCS in clinical practice on the basis of adequate randomized controlled treatment trials.